Improving Student Learning Outcomes of Grade VI in Science Subjects Through the Problem Based Learning Model - Maula, Iffatul; Wiratsiwi, Wendri (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
The purpose of this study is to improve student learning outcomes in the subject of social studies on the topic of international relations by implementing the Problem Based Learning (PBL) model in class VI of UPT SD Negeri Sumurgung 1 Tuban. This study focuses on the problem that arises in the form of low achievement of student learning outcomes in the subject of social studies on the topic of international relations due to the use of less effective learning models. The PBL model was chosen because it is able to encourage students to think critically, work together and solve problems relevant to everyday life. This study design uses Classroom Action Research (CAR) which is implemented in two cycles. The subjects in the study consisted of 12 students, including 7 male students and 5 female students. Each cycle includes the steps of planning, implementation, observation and reflection. Data were collected through observation sheets and written test results. This study shows that the use of the PBL model provides a significant increase in student learning outcomes. In cycle I, the average score reached 68.75 with a classical completion percentage of 41.66%. While in cycle II, the average score reached 84.58 with a classical completion percentage of 83.33%. Thus, it was concluded that the implementation of the Problem-Based Learning model was effective in improving student learning outcomes in the science subject of international relations. The researcher recommends that this model be used in teaching other subjects to improve student learning outcomes.